Abdominal cystic lymphangioma in a term newborn: A case report and update of new treatments. Issue 8 (February 2017) - Amodeo, Ilaria; Cavallaro, Giacomo; Raffaeli, Genny; Colombo, Lorenzo; Fumagalli, Monica; Cavalli, Riccardo; Leva, Ernesto; Mosca, Fabio
Abstract: Introduction: Lymphatic malformations are benign anomalies derived from the abnormal development of lymphatic channels. Usually asymptomatic, they can cause compression on adjacent structures or present acute complications (bleeding or infection). Small asymptomatic lesions can be conservatively managed since the possibility of spontaneous regressions is described, while symptomatic lesions require active management. Less invasive therapeutic options are now preferred instead of surgery (sclerotherapy, laser therapy). However, there are not uniform therapeutic protocols. Case Report: We present the case of a term newborn with an abdominal cystic lymphangioma extending from the umbilical to the right inguinal area, reaching the medial surface of the right tight. Despite its large dimensions, which classically request surgical management, the patient was by chance asymptomatic, and the mass did not determine compression on the surrounding organs. Therefore, conservative management was tried, and a close clinical and radiological follow-up was started. This approach permitted a spontaneous regression of the mass and to avoid major surgical intervention. Conclusion: Our purpose is to underline the possibility of conservative management of the major multicystic masses and to focus on less invasive therapeutic options, like sclerotherapy, oral therapy, and laser therapy.